Estimation of Time of Death through Observation of Microbiota Changes in the Oral Cavity - Oktaviana, Fahriza R.; Gultom, Ferry P.; Pasaribu, Roben S.; Auerkari, Elza I. (Universitas Sam Ratulangi, 2025)
Abstract: Various methods for estimating post-mortem (PMI) have been investigated such as rigor mortis, livor mortis, molecular, chemical, and forensic entomology (insect) methods. However, these methods have weaknesses, therefore researchers are looking for more accurate methods in determining the time of death of a person. Molecular methods are unreliable due to the degradation of DNA, RNA, and proteins in corpses over time. In different parts of the body, the amount of diversity of microbes will be different. The oral cavity is the most abundant microbial area among other parts of the body due to its continuous exposure to the respiratory and digestive systems. This area has great potential in estimating time intervals of death because of its ease of access and the types of microbiomes that predominate at any given time. Therefore, this narrative review was conducted to describe studies that used oral microbiota communities to estimate post-mortem intervals. Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes are the dominant microbial types found in corpses. Firmicutes became one of the dominant bacterial phyla in the early stages of decomposition. Actinobacteria were found to decrease as PMI increased. Studies have shown that the oral microbiome has excellent potential as a parameter to determine the post-mortem interval. However, further research is needed with more complex environmental conditions such as different humidity and temperature. In addition, further research requires more samples of human remains to obtain more valid results. Keywords: oral microbiome; post-mortem interval; human identification; forensic odontology